"Anak Abah VS Warga 58%" Etnografi Virtual: Analisis Wacana Pertengkaran Politik Warganet Indonesia di Kolom Komentar di Kolom Komentar di Media Sosial - Putri Ayu Hidayatur Rafiqoh; Siswanto; Rosalina Kumalawati (Mediakom : Jurnal Ilmu Komunikasi, 2026)
This study analyzes the dynamics of political debates on social media following the 2024 Presidential Election, focusing on the group identities of “anak abah” and “warga 58%” through a virtual ethnography approach. The findings highlight four key points. First, identity politics demonstrates a stronger and more enduring bond than the electoral moment itself, as group identities are constructed through symbols, language, and emotional experiences that persist beyond the political event. Second, collective emotions such as anger and pride do not dissipate after the campaign; instead, they continue to reinforce solidarity through ongoing digital interactions. Third, social media algorithms intensify the persistence of these conflicts by creating spaces that circulate similar content and prolong cycles of debate. Fourth, this phenomenon reflects symbolic polarization, in which labels such as “anak abah” and “warga 58%” function as markers of political identity that extend beyond the presidential election in which they originated. Thus, social media becomes a stage for reinterpreting political reality, where citizens’ real-world choices are transformed into concise, symbolic, and emotionally charged digital narratives.